Modern Monetary Theory: A Wrong Compass for Decision-Making - Françoise Drumetz; Christian Pfister (Intereconomics)
Abstract In the last few years, the so-called Modern Monetary Theory (MMT) has been gaining prominence in the media and the public. This article presents the MMT approach to money and monetary policy, and discusses its recommendations regarding fiscal policy and aggregate demand management, the structural policies it advocates as well as the international aspects of MMT. Overall, it appears that MMT is based on an outdated state of economic science and that its claims regarding economic policies are much exaggerated: The meaning of MMT is more that of a political manifesto than of a genuine economic theory.